2020
DOI: 10.1113/jp279129
|View full text |Cite
|
Sign up to set email alerts
|

A 7‐day high‐fat, high‐calorie diet induces fibre‐specific increases in intramuscular triglyceride and perilipin protein expression in human skeletal muscle

Abstract: Key points We have recently shown that a high‐fat, high‐calorie (HFHC) diet decreases whole body glucose clearance without impairing skeletal muscle insulin signalling, in healthy lean individuals. These diets are also known to increase skeletal muscle IMTG stores, but the effect on lipid metabolites leading to skeletal muscle insulin resistance has not been investigated. This study measured the effect of 7 days’ HFHC diet on (1) skeletal muscle concentration of lipid metabolites, and (2) potential changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 65 publications
1
21
0
Order By: Relevance
“…The histochemical demonstration of the LD microenvironment by the current study (Whytock et al .) complements the observation that subcellular compartmentalization of lipid metabolites is associated with discrepant metabolic measures (Perreault et al . 2018).…”
supporting
confidence: 79%
See 3 more Smart Citations
“…The histochemical demonstration of the LD microenvironment by the current study (Whytock et al .) complements the observation that subcellular compartmentalization of lipid metabolites is associated with discrepant metabolic measures (Perreault et al . 2018).…”
supporting
confidence: 79%
“…2012). In the current paper, the HFHC diet increases muscle PLIN2‐positive LDs while muscle diacylglycerol and ceramide, key intermediates capable of triggering cellular dysfunction, remained unchanged (Whytock et al .). These observations support the role of free fatty acid sequestration in modifying the metabolic effect of high‐fat exposure.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…Overall, 7 days of HFHC diet did not induce changes in whole-body insulin sensitivity (Matsuda ISI), or indices of hepatic or muscle insulin resistance. This was somewhat surprising considering previous studies have reported a reduction in measurements of insulin sensitivity following the same 7-day HFHC diet in young, healthy lean individuals [35,36,48,49]. The current study was novel, however, in measuring and characterising high cardio-respiratory fitness and high physical activity levels of the participants.…”
Section: Discussionmentioning
confidence: 70%